2006
DOI: 10.1007/s10979-006-9038-8
|View full text |Cite
|
Sign up to set email alerts
|

Adults' judgments of children's coached reports.

Abstract: This study investigated adults' judgments of the honesty of children's coached true and fabricated mock testimony. Adults saw video clips of children testifying in a mock court about a true or fabricated event in their lives. They were asked to make an assessment of the truthfulness of the testimony, and respond to questions about their perception of children's credibility. Half of the adults saw children testifying after a competence examination, and the other half saw children testifying without a competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
66
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 29 publications
10
66
3
Order By: Relevance
“…Thus, even though the video observers' deception detection performance was better than chance level, their performance was not better than the performance by the observers in the other conditions. This finding supports previous research showing that when observers only have access to a videotaped statement, it is a very difficult task to assess a child's veracity (Talwar & Lee, 2002;Talwar, Lee, Bala, & Lindsay, 2006).…”
Section: Adults' Deception Detection Performancesupporting
confidence: 91%
“…Thus, even though the video observers' deception detection performance was better than chance level, their performance was not better than the performance by the observers in the other conditions. This finding supports previous research showing that when observers only have access to a videotaped statement, it is a very difficult task to assess a child's veracity (Talwar & Lee, 2002;Talwar, Lee, Bala, & Lindsay, 2006).…”
Section: Adults' Deception Detection Performancesupporting
confidence: 91%
“…Importantly, the accuracy levels displayed by parents in this study were higher than those found in the literature examining laypersons detection of lying (49% to 51%), suggesting that parents may possess a unique skill they apply during detection (e.g., Edelstein, Luten, Ekman, & Goodman, 2006;Leach et al, 2004;Talwar et al, 2006). Moreover, parents in this study outperformed parents in other studies (Chahal & Cassidy, 1995;Oldershaw & Bagby, 1997; who were attempting to detect the lies of children other than their own.…”
Section: Discussioncontrasting
confidence: 66%
“…Using a different methodology, Herman (2005) estimated that the overall error rate for judgements about uncorroborated CSA allegations is at least 0.24. The hypothesis that, in the absence of corroboration, most MHPs are unable to reliably distinguish between children's-or, for that matter, adults'-true and false reports of past events, including reports of sexual abuse, is supported by a large body of empirical research and syntheses of existing research (Bond & DePaulo, 2006;Crossman & Lewis, 2006;Faust & Ziskin, 1988;Fisher, 1995;Fisher & Whiting, 1998;Goodman et al, 2002;Herman, 2009;Hershkowitz et al, 2007a;Horner et al, 1993a;Leach, Talwar, Lee, Bala, & Lindsay, 2004;Lindblad & Lainpelto, 2008;Melton & Limber, 1989;Orcutt, Goodman, Tobey, Batterman-Faunce, & Thomas, 2001;Poole & Lindsay, 1998;Realmuto, Jensen, & Wescoe, 1990;Realmuto & Wescoe, 1992;Talwar, Lee, Bala, & Lindsay, 2006;Vrij, Akehurst, Brown, & Mann, 2006).…”
Section: Discussionmentioning
confidence: 99%